THE EFFECT OF ADDING CYPERUS ROTUNDUS TO DECREASE PEROXIDE LEVEL AT WASTE COOKING OIL - Christ Kartika Rahayuningsih; Indah Lestari; Inggit Rianingtyas (Jurnal Kesehatan Prima, 2016)
Abstract: Jelantah (waste cooking oil) is the oil which is used repeatedly and posseses adequate high peroxide level, which can lead to cancer when the oil is used continually. The addition of antioxidants in the oil is aimed to inhibit the oxidation process, where the Cyperus rotundus is one of the wild plants that contains a high potential as natural antioxidants. Therefore, the purpose in this research is to find out the influence of additional Cyperus rotundus to decrease peroxide level at waste cooking oil. The method applied in this research was experimental with quantitative analysis using iodometric method to 6 samples of waste cooking oil which were randomly choosen. A sample criterion was waste cooking oil which had been used for more than three times by fried seller at Beluru village, Sidoarjo district. Based on the samples analyzed, average peroxide value of waste cooking oil before the additional was a large amount of 16.5309 mEq / 1000 grams, the average value of peroxide after the addition of Cyperus rotundus as much as 5 g of 10.9604 mEq / 1000 g, and the addition 30 g Cyperus rotundus a large amount of 7.3508 mEq / 1000 g, the addition of 50 g Cyperus rotundus a large amount of 5.0103 mEq / 1000 g. The research was analyzed by One Way Anova, and it can be concluded that there was no significant effect on the peroxide of wastecooking oil with the addition of Cyperus rotundus.